Aryl-Aryl Bond Formation by Ullmann Reaction: From Mechanistic Aspects to Catalyst - Jiang, Jie; Du, Liyong; Ding, Yuqiang (Mini-Reviews in Organic Chemistry, 2020)
Aryl-aryl bond formation is one of the most important tools in modern organic synthesis. Therefore, there is a high level of interest to develop green, effective reaction system to obtain biaryls. This review summarized the recent advances in the metal-catalyzed Ullmann reaction in which the aryl-aryl bond was formed directly. Furthermore, different types of catalytic mechanisms, especially the surface reaction, have been summarized to help the design of the catalyst.
Keywords: metal-catalyzed synthesis